The Criminal Liability of Minors in the Case of Offenses with a Duration of Consummation - DASCĂL, Teodor (Journal of Legal Studies, 2014)
The paper in centered around the criminal liability of minors in the case of offenses that have a duration of consummation, when, after committing a criminal offense, the minor becomes of age and the offense has consequences that occur after the age of eighteen, as well as in the situation where the offense has been committed by a minor that is not criminally responsible, but the consequences of the offense occur after the minor becomes of criminal age; in these cases, the problem of establishing the way in which the minor will or will not be held accountable arises.